Desarrollo de un prototipo para el servicio de autenticación central de usuarios en aplicaciones web. - Aguilar Soto, Wilmer Antonio (2019)
In recent years the use of Web applications, has evolved constantly, having its impact directly on authentication of users for multiple applications; so the user must manage several IDs username and associated password, which is uncomfortable for them. To this end, the following question was raised would ¿ Through a single authentication, using the central authentication service for multiple applications, will a better management of the roles of each user be carried out, giving a better security and optimization of resources?. The present TT was developed in a simulated environment and, as a case study, it was implemented in the Telecommunications and Information Unit (UTI) of the National University of Loja (UNL). For this purpose, two Systematic Literature Review (SLR) were developed, based on Bárbara Kitchenham's protocol, resulting in the selection of 30 primary studies, whose main findings allowed to establish the characteristics that Web applications must comply to be integrated with the Central Authentication Service (CAS) protocol. For the storage of user information, a hierarchical structure was designed and developed on the OpenLDAP server, along with a Web Service, which contains authentication and administration functions. The Development & Operations (DevOps) approach and cycle were used jointly for the integration of the previously selected Web applications and evaluation of the proposed prototype by the staff of the UTI of the UNL. In this way we could determine that the proposed prototype resulted in a positive score of 99,42% in testing functionality and 100% in tests for acceptance by staff of UTI, corroborating its operation and concluding in its implementation in this institution of higher education, as work future recommends the use of an Application Programming Interface (API) using the CAS Protocol, for those applications developed in different programming languages and have no direct support with external authentication services.